40 Pre-procedure anxiety: the origin of pain during implantation of cardiac implantable electronic devices. (May 2019) - Senior, Jonathan; Liu, Boyang; Jani, Ayman; Apostolakis, Michail; Goyal, Deepak; Taylor, Robin; Foster, Will; Brewster, Nicola; Wilson, David G
Abstract : Introduction: Cardiac implantable electronic device (CIED) implantation is an increasingly prevalent part of cardiac rhythm management. Adequate procedural pain management is central to the patient experience. The Association of Anaesthetists of Great Britain guidelines state that operators should develop techniques that permit the patient to undergo the procedure with minimum stress and maximum comfort. We developed an audit tool to assess the quality of pain management, and have evaluated the causative factors that can be targeted to optimise the patient experience. Methods: A prospective audit was collected over a 23-month period using a patient self-reporting questionnaire. Patients were asked to score their anxiety level prior to, and their pain during the procedure on a 0–10 visual scale. Finally, patients were asked whether the pain matched their expectations. Results: 349 near consecutive patients (67% male, age 75±13 years) were included in this audit. There were 167 pacemaker implantations, 42 implantable cardioverter defibrillators, 98 cardiac resynchronisation devices, 13 lead revisions and 29 generator changes. A majority of patients (219, 63%) reported no/mild pain, with 172 (49%) reporting the pain to be less than expected. However, 71 (21%) patients reported the pain to be more than expected, with 56 (16%) reporting severe pain. We wanted to clarify which factors were important in influencing patients' experience of pain during their procedure. Using a logistic regression model, we investigated whether gender, weight, pre-implant anxiety, device complexity and operator predicted patients' experience of pain. Complex devices are defined as CRT, ICD, or any procedure involving lead extraction. The logistic regression model was statistically significant (χ2 18.8, P=0.002), explaining 14.8% (Nagelkerke R2) of the variance in severe pain and correctly classified 85.8% of cases. Patients with high pre-procedural worry were 2.7 times more likely to experience severe pain. Additionally, female patients were 3.2 times more likely to experience severe pain. Device complexity, operator and patient weight had no impact on pain (figure 1 ). Interestingly, there was a weak positive correlation between the quantity of lidocaine usage and perceived pain (R=0.20, P<0.001). It is possible that operators are using more local anaesthetic if patients are complaining of increased intra-procedural pain. Conclusion: The majority of patients underwent CIED implantation with minimum discomfort, though an important minority reported severe pain during the procedure. The most significant predictor of pain was a high level of pre-procedure anxiety and therefore interventions targeted at reducing pre- and peri-implant anxiety, particularly in women, warrant further investigation as a means to reduce pain during CIED implantation. Conflict of Interest: Nil